Superior canal dehiscence syndrome in children: a case report - Schell, Angela; Servais, Jérôme J.; Hörmann, Karl; Hülse, Manfred; Hülse, Roland (International journal of pediatric otorhinolaryngology, 2015)
Initially described in 1998, superior semicircular canal dehiscence syndrome (SCDS) has become a well-studied neurootologic entity in adults by now. Unfortunately, experience with children is limited and a diagnostic and therapeutic algorithm is lacking. The article therefore wants to provide an overview of the existing literature on superior semicircular canal dehiscence syndrome in children. Furthermore a diagnostic algorithm for daily clinical life based on a case report from an eleven-year-old girl is presented.